Identification of the species origin of commercially available processed food products by mitochondrial DNA analysis - Murugaiah, Chandrika; Mustakim, Maimunah; Mohd Noor, Zainon; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Legislation concerning the safety assessment and labelling of foodstuffs has been implemented in many countries. Consequential to a number of cases of food adulteration reported globally, a fast and reliable detection method for the food traceability is required in ensuring effective implementation of food legislation in a country. In this study, PCR-RFLP technique based on cyt b gene has been tested for its suitability for these purposes. This method combines the use of a pair of universal primer that amplifies a 359 bp fragment on the cyt b gene from meat muscle DNA and restriction enzyme analysis. Analysis of experimental beef frankfurter, minced beef, pork frankfurter and pork cocktail samples demonstrated the suitability of the assay for the detection of the beef (Bos taurus) and pork (Sus scrofa), but not applicable for some processed food, particularly detection of mackerel (Rasterelliger brachysoma), sardine (Saedinella Fimbriata) and tuna (Thunnus tonggol) origin in canned food. Commercial frauds through species mislabelling or misdescribed were not detected. The assay is demonstrated applicable for routine analysis of meat traceability of foodstuffs and legislation purposes, if sufficient availability of detectable mtDNA in the foodstuffs is ensured.